2021
DOI: 10.1523/eneuro.0425-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

FKBP51 in the Oval Bed Nucleus of the Stria Terminalis Regulates Anxiety-Like Behavior

Abstract: for their excellent technical assistant and support. We thank Stefanie Unkmeir, Sabrina Bauer and the scientific core unit Genetically Engineered Mouse Models for genotyping support. We also thank Jessica Keverne for language editing the manuscript. The graphical abstract was created with Biorender.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
(112 reference statements)
2
12
0
Order By: Relevance
“…This suggests that no tolerance develops to the pharmacological effect. Overall, our data supports the importance of FKBP51 inhibition for anxiety-like behaviors and also challenges new evidence on the role of FKBP51 in anxiety regulation [50].…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that no tolerance develops to the pharmacological effect. Overall, our data supports the importance of FKBP51 inhibition for anxiety-like behaviors and also challenges new evidence on the role of FKBP51 in anxiety regulation [50].…”
Section: Discussionsupporting
confidence: 76%
“…This may explain why levels of Fkbp5 after acute stress return to homeostatic levels sooner in females than males ( Bourke et al, 2013 ). It is likely that increased chromatin accessibility of Fkbp5 in double-hit males is the result of a latent impact of the first hit of stress, and could itself confer protection against anxiety-like phenotypes, consistent with findings showing that overexpression of Fkbp5 in discrete brain regions induces anxiolytic phenotypes ( Engelhardt et al, 2021 ). Chromatin accessibility of Zbtb16 was also different in males and females, with double-hit stress inducing significant chromatin remodeling in males but not in females.…”
Section: Discussionsupporting
confidence: 84%
“…Despite our findings that activation of Corticotropin-Releasing Factor (CRF)-expressing neurons contained within the oval nucleus of the Bed Nucleus of the Stria Terminalis (BNSTov) produces pro-resilient behavioral responses, several studies have reported that this activation induces negative emotional states. [3][4][5][6][7][8] Previously, we show that BNSTov CRF activation had a pro-social effect only after cumulative stress exposure 1 , suggesting a role for BNSTov CRF neurons in potentially promoting cooperative sociality under stressful conditions. This adaptive function confers an evolutionary advantage.…”
Section: Resultsmentioning
confidence: 82%